The Collections of Miraculous Stories on the Buddhāvataṃsaka-sūtra - Jing Liu (Távol-keleti Tanulmányok)
This paper examines the three primary Chinese translations of the Buddhāvataṃsaka-sūtra— an extensive Mahāyāna text foundational to the Huayan School during the Sui and Tang Dynasties. This study provides a comprehensive introduction to each translation, tracing its dissemination across China, and further investigates the contributions and legacy of the five patriarchs of the Huayan School.